The construction of a supramolecular polymeric rotaxane from bipyridine-ruthenium and cyclodextrin - Liu, Yu (2011)
A luminescent supramolecular link is constructed by a very simple method using bipyridine-ruthenium and cyclodextrin, which displays not only a quasi-linear structure, but also a satisfactory fluorescence emission in both solution and the solid state.